Deliberative and spontaneous cognitive processes associated with HIV risk behavior. - Grenard, Jerry; Ames, Susan; Stacy, Alan (Journal of Behavioral Medicine, 2013)
Dual process models of decision-making suggest that behavior is mediated by a spontaneous behavior selection process or by a more deliberative evaluation of behavioral options. We examined whether the deliberative system moderates the influence of spontaneous cognition on HIV-risk behaviors. A measure of spontaneous sex-related associations (word association), a measure of deliberative working memory capacity (operation span), and two measures of sexual behavior (condom use and multiple partners) were assessed in a cross-sectional study among 490 adult drug offenders. Significant effects were observed among men but not among women in two latent interaction models. In a novel finding, the accessibility of spontaneous safe sex-related associations was significantly more predictive of condom use among men with higher working memory capacity than among men with lower capacity. These results have implications for the design of interventions to promote safe sex practices.